TANGGUNGJAWAB PERAWAT TERHADAP PASIEN DALAM PELIMPAHAN KEWENANGAN DOKTER KEPADA PERAWAT - Gunawan Aineka; Firdaus '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Legally Indonesia has the legal regulation of health and professions related to health . Along with the development of more advanced medical world , the processes and mechanisms of health care also increased from various aspects . So that not a few who have problems or contrary to law . Based on these problems , the thesis is to formulate three formulation of the problem , namely : first , the responsibility of nurses to patients in the delegation of authority of doctors to nurses , second , the mechanism of transfer of authority of doctors to nurses , third , the extent to which medical action limits of delegated authority doctors to nursesThis type of research can be classified into types of juridical empirical research , because in this study the authors conducted research literature study and discussions with academic experts and field practitioners .data sources used , the primary data , secondary data and data tertiary , technical data collectors in this study with interviews , and literature.From the research, there are three main issues that can be inferred , the first responsibility of nurses to patients in the delegation of authority of doctors to nurses is on the giver command " Article 1365 Civil Code " . Second , the mechanism of transfer of authority of doctors to nurses in writing , third , limit the authority delegated medical acts doctors to nurses located on professional ethics , professional standards and the role and functions of each profession . Suggestions author , socialization government against statutory provisions and professional health should be better again , make the Indonesian people aware of their rights and obligations in health care and affirmative action against against any violation of the law.Keywords: responsibility, delegation, medic